The Effect of Practical-Based Jigsaw Strategy on Science Process Skills of Students - Getrudis Wilhelmina Nau; Aloysius Djalo (Scientiae Educatia: Jurnal Pendidikan Sains, 2019)
A professional science teacher is a teacher who not only understands the basics of science but also understands the skills of the scientific process. However, the results of the tracer study show that science process skills (SSP) from Unwira Biology Education graduates is still low. Therefore, the right strategy is needed to create graduates who understand SSP, like practical jigsaw-based cooperative strategies. The purpose of this study was to determine the effect of practical-based jigsaw strategies on the science process skills of biology education students. This research is a quasi-experiment. The sample used was the fourth-semester students of class A and Class B. Class A as a control and class B as an experimental. The results showed that the average score of students' SPS in the experimental class was 90.4 while in the control class was 62.67. After being analyzed using the Independent-Sample t-Test, it showed a significant effect with a value of 0.036. This research concludes that the practical-based jigsaw strategy influences student science process skills.